Faktor Lingkungan Sebagai Faktor Risiko Derajat Kepaparan Penyakit Paru Obstruktif Kronik Pada Lansia - Novie, Novie Elvinawaty Mauliku; Desintra, Desinta Estri Dianis (Faculty of Health Science and Technology, University of Jenderal Achmad Yani, 2019)
Chronic Obstructive Pulmonary Disease (COPD) is a disease characterized by limited airflow that is not entirely reversible. The People with COPD in Indonesia are estimated toreach 4.8 million with a prevalence of 5.6% and rank first with morbidity(35%).COPD cancause damage to the structure of the respiratory tract and result in narrowing of therespiratory tract. This study aims to determine the relationship of environmental factors withthe severity of COPD in the elderly at BBKPM Bandung. The study design was used crosssectional.The population of this study was all the elderly who treated at BBKPM Bandung in2017 as many as 51 people with a total sampling technique. A questionnaires and GPSDistance Meters were used as the research instruments. The results showed that there was arelationship between smoking history (p = 0.038) and house distance to pollutant sources (p= 0.014). Whereas the unrelated variables were occupational history (p = 0.956) andbiomass exposure at home(p = 0.189), it can be concluded that there is a correlation betweenthe history of smoking and distance of the house with COPD severity in the elderly.